2023
DOI: 10.1097/mco.0000000000000991
|View full text |Cite
|
Sign up to set email alerts
|

Glutamate and obesity – what is the link?

Lila Chaouche,
Félix Marcotte,
Ina Maltais-Payette
et al.

Abstract: Purpose of review Many studies using metabolomics have tried to unravel the metabolic signature of obesity and understand the pathophysiology of this complex and heterogeneous disease. Circulating levels of the amino acid glutamate have been consistently associated with obesity and more specifically with measurements of abdominal fat accumulation. The purpose of this narrative review is to highlight recent studies documenting this association. Recent findings … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 32 publications
0
1
0
1
Order By: Relevance
“…Despite we found similar serum D-serine levels between diabetic and non-diabetic subjects, L-serine and L-glutamate were increased in diabetic compared to non-diabetic group, consistently with previous blood metabolomics evidence [ 16 , 17 ]. In line with other studies [ 90 ], we also observed a positive correlation between serum L-glutamate concentration, BMI and visceral adiposity in both non-frail and frail participants. Although the biological mechanisms responsible for this association are still unclear, considering that glutamate signaling modulates the immune system [ 91 ] and that increased VAT promotes systemic inflammation [ 92 ], elevated blood L-glutamate levels could represent a metabolic signature underpinning the abnormal increase in oxidative stress and inflammation associated with obesity.…”
Section: Discussionsupporting
confidence: 93%
“…Despite we found similar serum D-serine levels between diabetic and non-diabetic subjects, L-serine and L-glutamate were increased in diabetic compared to non-diabetic group, consistently with previous blood metabolomics evidence [ 16 , 17 ]. In line with other studies [ 90 ], we also observed a positive correlation between serum L-glutamate concentration, BMI and visceral adiposity in both non-frail and frail participants. Although the biological mechanisms responsible for this association are still unclear, considering that glutamate signaling modulates the immune system [ 91 ] and that increased VAT promotes systemic inflammation [ 92 ], elevated blood L-glutamate levels could represent a metabolic signature underpinning the abnormal increase in oxidative stress and inflammation associated with obesity.…”
Section: Discussionsupporting
confidence: 93%
“…Ингибирование глутаматных рецепторов положительно сказывается на центральном накоплении жира (окружность талии, площадь висцеральной жировой ткани и др.) [40]. Хемореактомный анализ показал, что Другие проблемы эндокринологии фонтурацетам может являться наиболее сильным ингибитором метаботропного глутаматного рецептора mGluR5 (IC50 = 35 нМ).…”
Section: хемореактомное исследование эффектов фонтурацетама: молекуля...unclassified
“…Glutamate is another amino acid linked to obesity. Circulating glutamate levels are positively associated with central obesity [93]. However, the underlying pathophysiological pathways responsible for this association are still unclear.…”
Section: Obesitymentioning
confidence: 99%